Nmap Network Exploration and Security Auditing Cookbook - Calderon, Paulino (Packt Publishing, 2021)
A complete reference guide to mastering Nmap and its scripting engine, covering practical tasks for IT personnel, security engineers, system administrators, and application security enthusiasts Key Features Learn how to use Nmap and other tools from the Nmap family with the help of practical recipes Discover the latest and most powerful features of Nmap and the Nmap Scripting Engine Explore common security checks for applications, Microsoft Windows environments, SCADA, and mainframes Book Description Nmap is one of the most powerful tools for network discovery and security auditing used by millions of IT professionals, from system administrators to cybersecurity specialists. This third edition of the Nmap: Network Exploration and Security Auditing Cookbook introduces Nmap and its family - Ncat, Ncrack, Ndiff, Zenmap, and the Nmap Scripting Engine (NSE) - and guides you through numerous tasks that are relevant to security engineers in today's technology ecosystems. The book discusses some of the most common and useful tasks for scanning hosts, networks, applications, mainframes, Unix and Windows environments, and ICS/SCADA systems. Advanced Nmap users can benefit from this book by exploring the hidden functionalities within Nmap and its scripts as well as advanced workflows and configurations to fine-tune their scans. Seasoned users will find new applications and third-party tools that can help them manage scans and even start developing their own NSE scripts. Practical examples featured in a cookbook format make this book perfect for quickly remembering Nmap options, scripts and arguments, and more. By the end of this Nmap book, you will be able to successfully scan numerous hosts, exploit vulnerable areas, and gather valuable information. What you will learn Scan systems and check for the most common vulnerabilities Explore the most popular network protocols Extend existing scripts and write your own scripts and libraries Identify and scan critical ICS/SCADA systems Detect misconfigurations in web servers, databases, and mail servers Understand how to identify common weaknesses in Windows environments Optimize the performance and improve results of scans Who this book is for This Nmap cookbook is for IT personnel, security engineers, system administrators, application security enthusiasts, or anyone who wants to master Nmap and its scripting engine. This book is also recommended for anyone looking to learn about network security auditing, esp...